Hands-on Training: Improving Speaking Skills through Games for Students and Care Takers of Panti Asuhan Sentosa, Belitung Darat, Banjarmasin - Murtiningsih, Tenny; Kailani, Ahmad; Farid, Rezqan Noor (Comment: an International Journal of Community Development, 2019)
Speaking is one of the four macro skills of English. It is also a productive skill that requires language learners to gain much exposure to use it. Accuracy and fluency are two elements to be used as parameters of speaking ability for foreign language learners. Apart from this, language learners still find it hard to express out their speaking ability in front of classroom as well as outside the class. Lack of self confidence, limited vocabulary acquisition, and English grammar have become obstacles for learners to develop their speaking ability. Through this hands-on workshop, we introduced three educational games, namely, hot seat, comic strip, and that’s an unusual view to students and teachers at panti Asuhan Sentosa Banjarmasin. These games are intended to make learning english more fun, to help students gain self confidence to use the language, and to boost cooperative work between students and teachers. The participants responded positively to the ideas and they would use those games as learning media.